Full Arch Implant Restoration Using Fast and Fixed Protocol: A Case Report - Thapa, D; Shrestha, P (Journal of Nepalese Prosthodontic Society, 2020)
Delivering a full arch implant restoration, which transits a patient from the frustrations of edentulism to the stability and function of a fixed prosthesis, is one of the most rewarding experiences in dentistry. With the advancement in digital technology, and with modified implant design and advance prosthetic options, what started as a two stage delayed loading procedure in the seventies, evolved to immediate implant placement in extraction sockets and even immediate loading of these implants in a growing number of indications.In this case report, the same evolution “immediate implant placement and immediate loading techniques” has been described using fast and fixed protocol from Bredent to rehabilitate patient’s failing dentition.